Novel human IgG1 and IgG4 Fc-engineered antibodies with completely abolished immune effector functions - Schlothauer, Tilman; Herter, Sylvia; Koller, Claudia Ferrara; Grau-Richards, Sandra; Steinhart, Virginie; Spick, Christian; Kubbies, Manfred; Klein, Christian; Umaña, Pablo; Mössner, Ekkehard (Protein engineering, design and selection, 2016)
Abstract Recombinant human IgG antibodies (hIgGs) completely devoid of binding to Fcγ receptors (FcγRs) and complement protein C1q, and thus with abolished immune effector functions, are of use for various therapeutic applications in order to reduce FcγR activation and Fc-mediated toxicity. Fc engineering approaches described to date only partially achieve this goal or employ a large number of mutations, which may increase the risk of anti-drug antibody generation. We describe here two new, engineered hIgG Fc domains, hIgG1-P329G LALA and hIgG4-P329G SPLE, with completely abolished FcγR and C1q interactions, containing a limited number of mutations and with unaffected FcRn interactions and Fc stability. Both ‘effector-silent’ Fc variants are based on a novel Fc mutation, P329G that disrupts the formation of a proline sandwich motif with the FcγRs. As this motif is present in the interface of all IgG Fc/FcγR complexes, its disruption can be applied to all human and most of the other mammalian IgG subclasses in order to create effector silent IgG molecules.